Multiplicity-dependent production of Σ(1385)± and Ξ(1530)0 in pp collisions at s = 13 TeV - Acharya, S.; Adamovã, D.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; Aleksandrov, D.; et al. (Springer Science and Business Media Deutschland GmbH, 2024)
The production yields of the Σ(1385)± and Ξ(1530)0 resonances are measured in pp collisions at √s = 13 TeV with ALICE. The measurements are performed as a function of the charged-particle multiplicity ⟨dNch/dη⟩, which is related to the energy density produced in the collision. The results include transverse momentum (pT) distributions, pT-integrated yields, mean transverse momenta of Σ(1385)± and Ξ(1530)0, as well as ratios of the pT-integrated resonance yields relative to yields of other hadron species. The Σ(1385)±/π± and Ξ(1530)0/π± yield ratios are consistent with the trend of the enhancement of strangeness production from low to high multiplicity pp collisions, which was previously observed for strange and multi-strange baryons. The yield ratio between the measured resonances and the long-lived baryons with the same strangeness content exhibits a hint of a mild increasing trend at low multiplicity, despite too large uncertainties to exclude the flat behaviour. The results are compared with predictions from models such as EPOS-LHC and PYTHIA 8 with Rope shoving. The latter provides the best description of the multiplicity dependence of the Σ(1385)± and Ξ(1530)0 production in pp collisions at √s = 13 TeV.
Keywords: Hadron-Hadron Scattering, Particle and Resonance Production; https://purl.org/pe-repo/ocde/ford#1.03.03